Ecological Awareness in Vālmikī’s Rāmāyana - Pokharel, Mohan Kumar (JODEM: Journal of Language and Literature, 2019)
The use of ecological awareness in the Vālmikī Rāmāyana is an exemplary case to deal with the postmodern environmental crisis. This research paper focuses on the connection between flora and fauna in this classical text. This study primarily interprets the discourses of the text which relates to the ecological awareness. At the same time, it also deals with the logic behind constructing the discourse of the poet through the activities of the characters and their thoughts related to ecology. To analyze the ecological awareness of the text, ecological study has been used as an overall theoretical approach. This study is significant in order to present how Vālmikī Rāmāyana manifests the ecological awareness to the postmodern people. The research approach adopted in this exploration is interpretive. The findings of this investigation provide the evidences that the epic has used ecological awareness in such a way that the epic impresses humans to make a balance between nature and creatures. The main conclusion drawn from this research is that Vālmikī is a far-sighted classical poet to make human beings aware of ecological crisis and its effects everywhere in the world.